The path of transcatheter aortic valve implantation: from compassionate to low-risk cases - Tamburino, Corrado (Eur Heart J Suppl, 2020)
Aortic stenosis (AS) is one of the most common valvular diseases in developed countries. Transcatheter aortic valve implantation (TAVI) has emerged as alternative to medical treatment or surgical aortic valve replacement (SAVR) in all symptomatic patients with severe AS. In 2002, Cribier performed the first human TAVI through a trans-septal approach in a 57-year-old man with severe AS. Since then, several trials have compared TAVI vs. SAVR over the years. Today, it is superior in terms of mortality to medical therapy in extreme-risk patients, non-inferior or superior to surgery in high-risk patients, and non-inferior to surgery and even superior when transfemoral access is possible in intermediate-risk patients. Interesting results emerged from the latest multicentre trials involving patients with severe AS who were at low risk for death from surgery, demonstrating that this therapy will be offered to younger people in the next future.